(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The principle of unity between general and special preparation in Kurash training considers their interconnection. In the early stages of multi-year sports training, general preparation plays a leading role, forming the foundation for functional capabilities and movement skills. For instance, Wrestlers who master acrobatics in the initial training stages can later perform complex technical-tactical movements successfully.